Management performance of the educational council as emerging factor for school-family-community integration (Revista Electrónica REDINE, 2020)
In the present study, the Educational Performance of the Educational Council was analyzed as an emerging factor for the Community-School-Community integration. Developing under the positivist paradigm, with a quantitative approach, supported by a non-experimental field design of a descriptive nature. The population consisted of four hundred and thirty (430) people and for the sample, a technique called intentional sampling was used, consisting of sixty-one (61): two (2) managers, nine (9) teachers, nine (9) spokespersons students and forty-one (41) representatives, all members of Educational Council. The techniques used in this investigation were the survey and direct observation. Three questionnaires were applied; conformed by closed questions with alternative answers. The validity of the instruments was carried out through the review of three subject matter experts and the reliability was determined with the Cronbach's Alpha coefficient, reaching values ​​of 0.9 for each of the instruments. It is concluded that there are coincidences in the opinions expressed by the subjects investigated, considering that the educational council is not working properly, which leads to a deficient process of School-Family-Community integration. It was also determined that the spokespersons are not fulfilling their responsibilities within the Educational Council.
Keywords: Management performance; educational council; school-family-community integration